Myocardial perfusion scintigraphy in the UK: insights from the British Nuclear Cardiology Society Survey 2000. (8th August 2005) - Kelion, A D; Anagnostopoulos, C; Harbinson, M; Underwood, S R; Metcalfe, M
Abstract : Background: The National Institute for Health and Clinical Excellence (NICE) has recently published a very positive technology appraisal of myocardial perfusion scintigraphy (MPS). This has important implications for service provision within the National Health Service, and an accurate knowledge of the current level of MPS activity is necessary. Methods: A postal questionnaire was sent to 207 nuclear medicine departments in the UK, requesting information about nuclear cardiology facilities, activity, and practice. Non-responding departments were sent a second questionnaire, followed where necessary by a telephone call. Results: A response rate of 61% was achieved; 52% of departments performed MPS, and these tended to have more gamma cameras than those which did not (median (25th–75th centile) 2.0, 1.5–2.5 v 1.0, 0.5–1.5; p = 0.02). The median number of studies performed was 256 (144–460). The estimated rate of MPS in the UK for the year 2000 was 1200 per million population. The median (25th–75th centile) waiting time for MPS was 16 (9–24) weeks. Pharmacological stress was used in 77% of studies, and a technetium-99m based radiopharmaceutical in 60% (two day protocol in 75%). Tomographic rather than planar imaging was performed in 88% of studies, of which 22% were ECG gated. A cardiologist was involved in reporting in 35% of studies. Conclusions: MPS activity in the UK remains low, and it tends to be provided as a low volume service with unacceptably long waiting times and a lack of involvement by cardiologists. The recent NICE appraisal may provide an impetus for further resourcing and development.